2005
DOI: 10.1074/jbc.m412123200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of EF-hand Domains and C2 Domain in Regulation of Enzymatic Activity of Phospholipase Cζ

Abstract: ). In the present structure-function analysis, deletion of EF1 and EF2 of the N-terminal four EF-hand domains caused marked reduction of phosphatidylinositol 4,5-bisphosphate (PI(4,5)P 2 )-hydrolyzing activity in vitro and loss of Ca 2؉ oscillation-inducing activity in mouse eggs after injection of RNA encoding the mutant. However, deletion of EF1 and EF2 or mutation of EF1 or EF2 at the x and z positions of the putative Ca 2؉ -binding loop little affected the Ca 2؉ sensitivity of the PLC activity, whereas del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 40 publications
5
111
0
1
Order By: Relevance
“…The EF-hand domains of most of these enzymes have limited or no ability to bind 4 Ca 2+ (Bairoch and Cox, 1990). A key exception to this is PLCζ, which is responsible for Ca 2+ oscillations in fertilized oocytes and exhibits a high sensitivity to Ca 2+ mediated through its EF-hand domain (Kouchi et al, 2005). Also it appears that the EF-hand domain of PLCδ1 is functionally important and regulates binding of the pleckstrin homology (PH) domain to PIP 2 in a Ca 2+ -dependent manner (Yamamoto et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The EF-hand domains of most of these enzymes have limited or no ability to bind 4 Ca 2+ (Bairoch and Cox, 1990). A key exception to this is PLCζ, which is responsible for Ca 2+ oscillations in fertilized oocytes and exhibits a high sensitivity to Ca 2+ mediated through its EF-hand domain (Kouchi et al, 2005). Also it appears that the EF-hand domain of PLCδ1 is functionally important and regulates binding of the pleckstrin homology (PH) domain to PIP 2 in a Ca 2+ -dependent manner (Yamamoto et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A study investigating the function of the domains in mouse Plcz1 has confirmed that the N-terminal EF-hand domains, especially EF-1 and EF-3, are essential for the function of Plcz1. The lack of the three EF-hand domains has been shown to result in a low level of Ca 2+ sensitivity [17] and loss of the Ca 2+ oscillations associated with fertilization in mouse eggs injected with EF domain RNA. This is in contrast to the activity of the full-length Plcz1, which can trigger Ca 2+ oscillations in mouse eggs [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…La PLC a la particularité d'être extrêmement sensible au calcium, et on pense qu'elle est naturellement active aux concentrations cytosoliques de calcium (10-100 nM) [36]. Cependant, dans le spermatozoïde, elle serait inactivée par la fixation de son domaine C2 (calcium-binding motif) à certains phosphatidylinositides comme le PIP3 et le PIP5 [37].…”
Section: Rôles Des Phospholipases Dans La Réaction Acrosomiqueunclassified